The Role of The Manpower Office In Fostering Micro, Small and Medium Enterprises (MSMES) In Parepare City - Bahruddin, Bahruddin; Wardhani, Wardhani; Rahmawati, Rahmawati (Economos : Jurnal Ekonomi dan Bisnis, 2023)
Micro, Small and Medium Enterprises (MSMEs) are the largest economic group in the economy in Indonesia and have proven to be the key to national economic security. It is proven that until now it remains part of the development program run by the government now including in the development, training and coaching of Micro, Small and Medium Enterprises (MSMEs) in the Regions. The purpose of this study is to determine the extent of the role of the Parepare City Manpower Office in fostering Micro, Small and Medium Enterprises (MSMEs). This study used descriptive analysis method, qualitative approach with simple regression analysis. Then based on data collection techniques using observation, documentation and interviews. Based on the results of the research and discussion conducted, it can be concluded that the results of the simple linear regression above can be interpreted as a regression coefficient for constant of 4.748 showing that if the variable Role of the Manpower Office is zero or fixed, it will increase MSMEs by 4,748 units. The value of the variable coefficient of the role of the Parepare City Manpower Office of 0.447 shows that if the variable role of the Parepare City Manpower Office increases by one unit, it will increase MSMEs by 0.447 units or 44.7%. Meanwhile, in the discussion of the role of the Manpower Office in coaching, it is only limited to providing motivation and entrepreneurship counseling for business actors. In addition, by assisting MSME actors and coaching, it has not been widely reached by all MSME actors, so there are MSME actors who have not received guidance from the Manpower Office in Parepare City.